Praticando Ciências - Lourdes , Dayane Freitas de; Cruz , Florisvaldo Gonçalves da; Martin , Maria Sinforosa; Martin , Marlene Dan e Maria Sinforosa; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf